Studi Literatur: Audit Deteksi Pengendalian Internal Pada Sistem Informasi Akuntansi Penjualan Tunai dan Retur Penjualan - Alifia Mutiara Rachmawati; Tarenza Noviandari; Michael Revelin Ervan Septian; Tri Ratnawati (Jurnal Riset Akuntansi, 2023)
Audit is a series of processes carried out by the auditor to obtain accurate evidence regarding the economic activity of a company. This article aims to determine the detection of internal controls on cash sales accounting information systems and sales returns. This article is a qualitative descriptive study of the literature. The results of this article are the accounting information system for cash sales and sales returns that have been carried out, there is a need for improvement, especially related to the company's internal control..